Theoretical Re-evaluations of Scaling Relations between SMBHs and Their Host Galaxies—1. Effect of Seed BH Mass - Shirakata, Hikari; Kawaguchi, Toshihiro; Okamoto, Takashi; Makiya, Ryu; Ishiyama, Tomoaki; Matsuoka, Yoshiki; Nagashima, Masahiro; Enoki, Motohiro; Oogi, Taira; Kobayashi, Masakazu A. R. (Frontiers in Astronomy and Space Sciences, 2017)
We explore the effect of varying the mass of a seed black hole on the resulting black hole mass -- bulge mass relation at $z \sim 0$, using a semi-analytic model of galaxy formation combined with large cosmological N-body simulations. When the mass of the seed is set at $10^5 M_\odot$, we find that the model results become inconsistent with recent observational results of the black hole mass -- bulge mass relation for dwarf galaxies. On the other hand, when we employ seed black holes of $10^3 M_\odot$ or select their mass randomly within a $10^{3 -5} M_\odot$ range, the resulting relation is consistent with observational results including the dispersion. We also find that black hole mass -- bulge mass relations for less massive bulges at $z \sim 0$ put stronger constraints on the seed BH mass than the relations at higher redshifts.